Composition of essential oil and fatty acids of Centaurea pichleri ssp. pichleri - Pelin Tastan; Tugce Fafal; Burcu Sümer Tüzün; Tuba Gönenç; Betül Demirci; Bijen Kivcak (International Journal of Secondary Metabolite, 2017)
In this study, the essential oil of Centaurea pichleri ssp. pichleri was obtained by hydrodistillation using a Clevenger-type apparatus. GC and GC/MS analyzes of the essential oil from Centaurea pichleri ssp. pichleri were determined the identification of 48 components representing 86.9% of the oil. With this analysis, the major component was found as hexadecanoic acid (31.4%). Subsequent to this component, other major components were caryophyllene oxide (6.4%), spathulenol (6.2%) and dodecanoic acid (4.5%). In addition to this, fatty acid methyl esters (FAMEs) from Centaurea pichleri ssp. pichleri were prepared for analyzes of fatty acids. By this test the amount of saturated fatty acid (SFA) was found as 47.79% with major fatty acid was stearic acid (18.64%). The amount of monounsaturated fatty acid (MUFA) was found as 16.88% with major fatty acid was oleic acid (14.20%). The amount of polyunsaturated fatty acid (PUFA) was found as 21.29% with major fatty acid was linoleic acid (15.20%). The results from this work were compared with the previous works in terms of essential oils and fatty acids.